We kill our own: towards a material ecology of farm life. Issue 4 (1st October 2016) - Broderick, Michael; Gleason, Sean
ABSTRACT: Drawing from fieldwork conducted over several months at a small Appalachian goat farm, experimental prose is coupled with affect-based critiques of human exceptionalism to uncover the rhythmic and vibrant relations of human/nonhuman interdependence (Gruen 5). Taking seriously the posthuman call to reimagine animal, human, and material relations, we envision farming as a rhythmic and affect-laden atmosphere of habit, co-constitution, and vibrant materiality.